A reflection on "Trash, teaching and the city". Issue 1 (2nd January 2018) - Majombozi, Ziyanda
Abstract : This is a commentary on Carina Truyts's photo essay entitled "Trash, Teaching and the City: The 'Big Hole Counter Narrative' project and the 'Urban Anthropology: Research Methods and Fieldwork' Course at Sol Plaatje University."